Rekomstruksi Filsafat Pendidikan Islam di Era Digital - Nur fitri; Roihan nabil hanif; Syifa ainur arstya (Ikhlas : Jurnal Ilmiah Pendidikan Islam, 2026)
The development of digital technology and artificial intelligence has fundamentally transformed how knowledge is acquired, managed, and disseminated, pressuring education especially Islamic education to adapt without losing its spiritual and moral identity. This study aims to analyze the reconstruction of educational philosophy in the digital era to establish a system that is solutive, relevant, and vision-oriented in producing generations who are intellectually competent while possessing high spiritual integrity. Using a qualitative approach involving literature study and qualitative content analysis, the study examines literature on the ontology, epistemology, and axiology of education, as well as previous research related to digital transformation and responsive curricula. The findings indicate that educational philosophy remains the primary foundation for determining the direction, objectives, and implementation of the educational process; the epistemological dimension requires reconstruction through an integrative paradigm that combines revelation, reason, empirical experience, and digital literacy; while axiology plays a strategic role in shaping ethical character amid unverified information flows. This finding underscores the urgency of transforming the paradigm from a textual approach toward a contextual-integrative one capable of harmonizing technological sophistication with the internalization of moral and spiritual values. The study's limitation lies in its conceptual nature without empirical verification; therefore, further studies are recommended to test the model through case studies, experiments, or surveys across various multicultural contexts.